The contest and control of Jerusalem's holy sites a historical guide to legality, status, and ownership - Breger, Marshall J. 1946-; Hammer, Leonard M. (Cambridge, United Kingdom New York, NY Cambridge University Press, 2023)
The Holy Places of Jerusalem's Old City are among the most contested sites in the world and the 'ground zero' of the Israeli-Palestinian conflict. Tensions regarding control are rooted in misperceptions over the status of the sites, the role of external bodies such as religious organizations and civil society, and misunderstanding regarding the political roles of the many actors associated with the sites. In this volume, Marshall J. Breger and Leonard M. Hammer clarify a complex and fraught situation by providing insight into the laws and rules pertaining to Jerusalem's holy sites. Providing a compendium of important legal sources and broad-form policy analysis, they show how laws pertaining to Holy Places have been implemented and engaged. The book weaves aspects of history, politics, and religion that have played a role in creation and identification of the 'law.' It also offers solutions for solving some of the central challenges related to the creation, control, and use of Holy Places in Jerusalem
Includes bibliographical references (pages 189-444) and index
Keywords: Shrines -- Law and legislation -- Jerusalem -- Sources; International Law; Shrines - Law and legislation; Sources; Jerusalem -- International status -- Sources; Middle East - Jerusalem